2020
DOI: 10.1101/2020.05.08.20095604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Migrants in Transit and Asylum Seekers in Mexico: An Epidemiological Analysis of the Covid-19 Pandemic

Abstract: BACKGROUND: Migrants could be disproportionately affected by the COVID-19 pandemic, yet little is known so far of the epidemiology of the disease among them, especially in low- and middle-income countries. OBJECTIVE: To describe the epidemiology of suspect cases of COVID-19 in migrants in transit and asylum seekers in Mexico, and to compare their characteristics with those of non-migrants. METHODS: This was a secondary analysis of information from the surveillance system of Mexico from January 1 to May 3 2020,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…[16] Risk conditions in this specific study population seemed to be less among migrants except for the case of pregnant women. [16] 3. Impact on social and socio-psychological wellbeing was assessed among international students in central China's Hubei province, showing that almost a quarter of the study population talked about the virus in regular conversations and almost half of the study population was unhappy due to the current lockdown condition.…”
Section: Transmission Dynamics and Hospitalisationmentioning
confidence: 75%
See 4 more Smart Citations
“…[16] Risk conditions in this specific study population seemed to be less among migrants except for the case of pregnant women. [16] 3. Impact on social and socio-psychological wellbeing was assessed among international students in central China's Hubei province, showing that almost a quarter of the study population talked about the virus in regular conversations and almost half of the study population was unhappy due to the current lockdown condition.…”
Section: Transmission Dynamics and Hospitalisationmentioning
confidence: 75%
“…The incidence risk among the observational studies varied from 0·12% to 2·08% in non-outbreak settings [16, 17], and from 5·64% to 21·15% in outbreak settings [18, 19], showing a high heterogeneity across the studies. Modelling studies also showed a high heterogeneity, which is due to different scenarios and timeframes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations